The level of awareness among Malay’s factory workers in Seberang Perai Tengah towards family Takaful concept / Nur Emisham Othman - Othman, Nur Emisham (2011)
The competition between conventional insurance and Islamic insurance (Takaful) is greater nowadays. Both industry providing a protection and saving schemes to the market but in term of operation and concept is different. Relating to this statement, level of awareness towards family takaful concept becoming a critical issue in takaful industry whether surrounding people are aware and understand about the concept of takaful and the differences between conventional insurance. Therefore, this research main purpose is to determine the level among Malays factory worker in Seberang Perai Tengah towards family takaful concept.